Monetary Policy in Singapore and the Global Financial Crisis - CHOW, Hwee Kwan (Institutional Knowledge at Singapore Management University, 2011)
Prior to the crisis the consensus amongst central bankers in advanced economies was that price stability, in the form of low and stable price inflation, was a top priority for monetary policy and could best be achieved by targeting interest rates (usually overnight) or monetary aggregates, such as Narrow Money (M1) and Broad Money (M2). Liquidity in the banking system could be flexibly adjusted on a daily basis through open market operations to increase or decrease the monetary base which would be transmitted to the rest of the economy through financial intermediation. Financial markets would then adjust longer-term interest rates relevant to the real economy, such as mortgage rates and 12-month corporate bond rates, and could largely be left alone to price risk and allocate credit efficiently, since financial markets were generally considered to be rational and efficient.